Peptide Electrophoretic Patterns of Cucumoviruses - Ahmad, Ismail; Scott, Howard A. (1986)
The peptide electrophoretic patterns of several cucumovirus isolates were compared using 15% polyacrylamide slab-gels. Both Staphylococcus aureus VB protease and a.-chymotrypsin partially digested the protein subunits of these virllies into peptides which produced different patterns when electrophoresed though the gels. Major differences were observed among peptide electrophoretic patterns of cucumber mosaic, peanut stunt and tomato aspermy viruses. Differences, if they do exist, among strains of the same virus were either in apparent or minor.